2009
DOI: 10.2522/ptj.20080260
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Promote Evidence-Based Practice in Pediatric Physical Therapy: A Formative Evaluation Pilot Project

Abstract: The pediatric physical therapists who took part in this project had positive attitudes toward evidence-based practice and made modest improvements in this area. It is critical for the profession to continue to investigate optimal strategies to aid practicing clinicians in applying research evidence to clinical decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 70 publications
0
48
0
Order By: Relevance
“…31,32 Despite some of these interventions showing promise with regard to shifting attitudes towards EBP, [25][26][27][28][29][30][31] not all have been effective in changing behavior related to EBP over time. 33,34 While the impact of the training program on EBP was not quantitatively assessed in this study, both clinicians and administrators observed substantial changes to participants' critical thinking and awareness of the interrelatedness of research and practice. Most striking was the number of participants who reported an increased commitment to practice improvement as well as shifts in clinical practice through revisions to practice guidelines and the development of patient and professional resources.…”
Section: Discussionmentioning
confidence: 88%
“…31,32 Despite some of these interventions showing promise with regard to shifting attitudes towards EBP, [25][26][27][28][29][30][31] not all have been effective in changing behavior related to EBP over time. 33,34 While the impact of the training program on EBP was not quantitatively assessed in this study, both clinicians and administrators observed substantial changes to participants' critical thinking and awareness of the interrelatedness of research and practice. Most striking was the number of participants who reported an increased commitment to practice improvement as well as shifts in clinical practice through revisions to practice guidelines and the development of patient and professional resources.…”
Section: Discussionmentioning
confidence: 88%
“…1,[3][4][5][6]10,[12][13][14][15][16]20,21,23,[28][29][30][31][32] Our review did not identify any other papers addressing knowledge broker experiences in rehabilitation. Although several studies 3,13,20,24 have suggested that knowledge brokers could help to close the knowledge-practice gap in health care, the effectiveness of such initiatives requires additional study.…”
Section: Discussionmentioning
confidence: 88%
“…We identified search terms through an iterative process that began with reviewing seminal 24 and emerging literature on knowledge translation, knowledge sharing, and research adoption [26][27][28][29][30][31][32][33][34][35] to determine the potential diversity in the literature with respect to knowledge brokering terms and approaches. Our aim was to identify and use search terms that maintained a focus on the exchange and acquisition components of knowledge and learning that are common to all definitions of knowledge brokers (see Box 1), without narrowing the search so much that potentially relevant papers would be missed.…”
Section: Search Strategymentioning
confidence: 99%
“…The recommendations made by respondents in our survey were similar to what was reported in the literature. Support in the form of provision of access to journals [12,26], journal availability in physiotherapy departments [33], providing continuing education courses [30], allowing more time for reading and discussing research reports [9,34] and provision of incentives Schreiber et al [35] were some of the strategies that were identified as facilitators to the use of EBP by others.…”
Section: Barriers To the Use Of Ebpmentioning
confidence: 99%